Desarrollo de habilidades adaptativas en estudiantes con discapacidad intelectual incluidos en las instituciones educativas de la educación general básica fiscal - Salazar Acosta, Tatiana Lilibeth (2017)
This work called "Development of the adaptive skills in students with intellectual disabilities included in basic general education" is based on a great issue that occurs in educational institutions when a student with disabilities to the classroom regular relationship that they can learn and that skills developed favouring their participation in society in a more autonomous way egalitarian and equitable. Research has been performed in the city of Guayaquil parish Chongon district 09d09 in two tax schools that welcome diversity in this case intellectual disability of mild and moderate, to severe and profound disabilities range the same district boasts an educational unit specialized for these students………